Implementasi Hukum Lalu Lintas dalam Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan - Andilolo, Jhordyan Pakiding; Tuasikal, Hadi; Markus, Dwi Pratiwi (UNES Law Review, 2024)
This research aims to analyze the implementation of traffic laws regulated in Law Number 22 of 2009 concerning Road Traffic and Transportation in Indonesia. The methodology used is normative juridical research which involves analysis of normatively applicable laws to understand their implementation in a wider context. The relevance of this research lies in the need to identify the effectiveness of the implementation of the Law, the level of public compliance with traffic rules, the performance of law enforcement officers, as well as the factors that influence the effectiveness of traffic law enforcement in Indonesia. This research contributes in the form of an in-depth understanding regarding the implementation of traffic laws in Law Number 22 of 2009, by highlighting aspects of safety, compliance and law enforcement. The research results show the implementation of traffic laws through consistent enforcement of rules, effective handling of violations, and cross-sector cooperation can improve traffic security and order. Recommendations for this research include increased outreach and education to the community, stricter law enforcement, regular evaluation of the performance of law enforcement officers, as well as investment in improving road infrastructure. In conclusion, the implementation of traffic law in Law Number 22 of 2009 in Indonesia has a significant impact on the safety of road users and improving traffic quality. With a holistic approach and cross-sector collaboration, it is hoped that a traffic culture that is good, safe, orderly and adheres to the rules can be created in society.